Endothelial Marker Proteins in Hyperhomocysteinemia - Jong, Sylvia C de; Stehouwer, Coen D A; Berg, Michiel van den; Vischer, Ulrich M; Rauwerda, Jan A; Emeis, Jef J (Thrombosis and Haemostasis, 1997)
Hyperhomocysteinemia is associated with severe, premature atherosclerosis and thromboembolism. The mechanisms involved in the atherogenic and thrombotic complications of hyperhomocysteinemia are not understood. It has been suggested that hyperhomocysteinemia predisposes to atherosclerosis by injuring the vascular endothelium. Whether hyperhomocysteinemia is independently associated with changed endothelial function, either in the absence or the presence of clinically manifest atherosclerotic disease, is, however, not known. Therefore we investigated, both in patients with peripheral arterial occlusive disease and in healthy individuals, whether plasma protein markers of endothelial function differed between subjects with, and subjects without hyperhomocysteinemia. We studied 80 individuals under the age of 56 years: healthy individuals with (n = 20) and without (n = 20) hyperhomocysteinemia and patients with peripheral arterial occlusive disease with (n = 20) and without (n = 20) hyperhomocysteinemia. The following endothelium-derived proteins were measured as markers of endothelial cell function: von Willebrand factor (vWf) and von Willebrand factor propeptide (vWf: Agll), tissue-type plasminogen activator (tPA), plasminogen activator inhibitor-1 (PAI-1), cellular fibronectin (cFN) and thrombomodulin ™. In addition we assessed C-reactive protein (CRP). vWf, vWf: Agll, tPA and CRP were significantly higher in the patients with peripheral arterial occlusive disease than in the healthy individuals. No differences in marker protein plasma levels were found between individuals with, and those without hyperhomocysteinemia, apart from vWf, which was significantly raised in hyperhomocysteinemic as compared to normohomocysteinemic patients. We did not find any evidence for an independent association between hyperhomocysteinemia and protein markers of endothelial cell function in healthy subjects.